Characterization of the neuropathic pain component contributing to myalgia in patients with myotonic dystrophy type 1 and 2 - Schmitt, Viviane; Baeumler, Petra; Schänzer, Anne; Irnich, Dominik; Schoser, Benedikt; Montagnese, Federica (Frontiers in Neurology, 2024)
Introduction Chronic muscle pain is common in myotonic dystrophies (DM). Little is known about its pathophysiology. We aimed to investigate the characteristics of the neuropathic pain component contributing contributes to the pathogenesis of chronic pain in DM. Methods Twenty-one DM1 and 32 DM2 patients completed pain questionnaires (Brief pain inventory–BPI, PAIN-DETECT, pain disability index–PDI) and underwent neurological examination, nerve conduction studies (NCS), quantitative sensory testing (QST, dorsum of the right hand and right thigh) and skin biopsy to determine the intraepidermal nerve fiber density (IENFD, distal and proximal site of lower extremity). NCS and QST results at the thigh were compared to 27 healthy controls and IENFD and QST at the dorsum of the hand to published reference values. Results The sensory profile of DM2 patients was characterized by a loss in thermal and mechanical detection, while DM1 patients showed reduced mechanical and heat pain thresholds and higher mechanical pain sensitivity. Both DM groups showed pressure hyperalgesia. IENFD was reduced in 63% of DM1 patients and 50% of DM2. The slightly higher pain interference and disability found in DM2 was rather due to age difference than disease. Conclusion Similar pain mechanisms likely occur in both DM1 and DM2, even though a tendency toward more pain sensitivity was observed in DM1 and more sensory loss in DM2. Both QST and reduced IENFD highlight the presence of peripheral nerve damage in DM. This must be considered for the best pain management strategies.